The Effect of Training Effectiveness on Employee Job Satisfaction - Bakar Sidik, Abu; Farida Ferine, Kiki; B., Mesra (International Conference Epicentrum of Economic Global Framework, 2025)
This study examines the position of risk assessment in correctional policy as the basis for granting conditional rights for inmates of narcotics crimes. This study is motivated by the increasing use of conditional rights in response to the problem of overcapacity in correctional institutions, which requires a rational, accountable, and risk-based decision-making mechanism. This research uses normative legal research methods with a statutory approach and a conceptual approach, through an analysis of Law Number 22 of 2022 concerning Corrections, related implementing regulations, as well as the political doctrine of criminal law and correctional theory. The results of the study show that risk assessment has been normatively placed as an integral part of correctional policies, especially in the process of granting parole. In the political framework of criminal law, risk assessment functions as an instrument to control state discretion so that the granting of conditional rights is carried out proportionately and in line with the interests of community protection. However, the existing regulatory framework has not fully provided detailed normative standards related to assessment indicators, inter-agency coordination mechanisms, and legal accountability for assessment results. This condition has the potential to reduce risk assessment to a purely procedural requirement. Therefore, this study emphasizes that strengthening the normative regulation of risk assessment is an urgent need, so that the policy of granting parole does not only function as an administrative mechanism, but truly becomes a risk-based, accountable, and balance-oriented correctional policy instrument between community protection and the fulfillment of prisoners' rights.